Models and perspectives concerning the identity of Jesus as healer - Dube, Zorodzai (Hervormde teologiese studies, 2018)
This study reviews various perspectives into the identity of Jesus as healer. There are two main perspectives – those that approach the identity of Jesus as healer from a theological perspective focusing on his personhood as messiah and those that use social scientific perspectives from sociology, psychology and anthropology. This study does not aim to evaluate or direct the reader towards a conclusion of Jesus’ identity, but only to review various perspectives. Based on analogies from Zimbabwe and comparative insights from the Mediterranean context from which the memory of Jesus survived, it is plausible that the identity of Jesus as healer should be found from the larger Greco-Roman context. Furthermore, given the various healers that existed during Jesus time both within the Jewish and Greco- Roman villages, the explanation of Jesus as healer is plausible from the various social scientific perspectives discussed.